2014
DOI: 10.1007/s00268-014-2513-3
|View full text |Cite
|
Sign up to set email alerts
|

ALPPS Offers a Better Chance of Complete Resection in Patients with Primarily Unresectable Liver Tumors Compared with Conventional‐Staged Hepatectomies: Results of a Multicenter Analysis

Abstract: This study provides evidence that ALPPS offers a better chance of complete resection in patients with primarily unresectable liver tumors at the cost of a high mortality. The technique is promising but should currently not be used outside of studies and registries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
255
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 254 publications
(272 citation statements)
references
References 45 publications
9
255
0
8
Order By: Relevance
“…22 Second, the completion rate of ALPPS significantly eclipses that of conventional 2-staged hepatectomy, with few patients failing to reach stage 2 of the procedure due to tumour progression. 23 Our results support the previous evidence of high feasibility of ALPPS. We found minimal interstage dropout, excellent FLR hypertrophy and a reduction in blood transfusion between stages in the late group without any compromise in perioperative outcomes.…”
Section: Discussionsupporting
confidence: 83%
“…22 Second, the completion rate of ALPPS significantly eclipses that of conventional 2-staged hepatectomy, with few patients failing to reach stage 2 of the procedure due to tumour progression. 23 Our results support the previous evidence of high feasibility of ALPPS. We found minimal interstage dropout, excellent FLR hypertrophy and a reduction in blood transfusion between stages in the late group without any compromise in perioperative outcomes.…”
Section: Discussionsupporting
confidence: 83%
“…A multicentric analysis revealed an 11-fold faster hypertrophy after ALPPS than after PVE (28). As hypertrophy is achieved more rapidly after ALPPS, the complete resection of the tumor could be performed in a shorter period of time, which offers some benefits: 1. the risk of disease progression between the two stages of the operation decreases (25,29); 2. the patient recovers more rapidly, decreasing the length of hospital stay (25); 3. the postoperative chemotherapy could be delivered sooner than in patients undergoing "twostage" operations (25).…”
Section: Discussion Discussionmentioning
confidence: 99%
“…Thus, major morbidity (Dindo-Clavien III or more) rates after ALPPS ranged between 27 and 41% in series presented until now (24,26,28,30,31). Moreover, the high mortality rates (up to 12.5% in most series) raise concerns about the indications, limits and surgical technique used for ALPPS (26,28). These factors were assessed in some recent papers and the authors recommended avoiding ALPPS in patients older than 60 years-old and in patients with hilar cholangiocarcinoma (28,32).…”
Section: Discussion Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 The ALPPS procedure has also been compared with the wellestablished technique of portal vein embolization/ ligation (PVE/PVL). 10 These comparisons have shown that 79% of patients undergoing ALPPS achieved cancer-free resection at three months compared with 58% in the PVE/PVL arm (odds ratio 2.80, confidence interval 1.12-6.98, p = 0.027). Volume increases per day were 11 times more rapid with ALPPS (34.…”
Section: Box 1: Case Descriptionmentioning
confidence: 99%